PENGARUH LOKASI, POTONGAN HARGA WORD OF MOUTH TERHADAP KEPUTUSAN EMBELIAN DI TOKO ROTI BUDI ASIH JUMAPOLO KARANGAYAR - Sinta Dewi Anggraeni, Pacundania; Handaruwati, Indah; Lyna, Lyna (HUMANIS: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2025)
This study aims to provide empirical evidence of the Influence of Location, Discounts, and Word Of Mouth on Purchasing Decisions. The population in this study were consumers of Budi Asih Bakery. The sample in this study was 40 people selected using the purposive sampling method, the study used primary data sources and secondary data sources, the data collection method used was the questionnaire method, the data that had been obtained was processed using SPSS. The results showed that the Location variable did not have a partial effect on purchasing decisions at Budi Asih Bakery, the Price Discount variable had a partial effect on Purchasing Decisions at Budi Asih Bakery, the Word Of Mouth variable had a significant effect on Purchasing Decisions at Budi Asih Bakery. The three variables Location, Discounts, Word Of Mouth Influence simultaneously on Purchasing Decisions.